Ethnography and Evaluation: Their Relationship and Three Anthropological Models of Evaluation - Brandon W. Youker (The Evaluation Center at Western Michigan University, 2005)
This paper examines the relationship between ethnographic research methods and evaluation theory and methodology. It is divided into two main sections: (a) ethnography in evaluation and (b) anthropological models of evaluation. Three levels of the leading anthropological models of evaluation are summarized, which include responsive evaluation, goal-free evaluation, and constructivist evaluation. In conclusion, (a) there is no consensual definition of ethnography; (b) in many circumstances, ethnographic evaluation models may be beneficial; and (c) ethnography can be used in evaluation but requires a high level of analysis to transform ethnographic data into useful information for eliciting an evaluative conclusion.